2023
DOI: 10.1002/med.21987
|View full text |Cite
|
Sign up to set email alerts
|

Communal interaction of glycation and gut microbes in diabetes mellitus, Alzheimer's disease, and Parkinson's disease pathogenesis

Rahul Shivaji Patil,
Rashmi Santosh Tupe

Abstract: Diabetes and its complications, Alzheimer's disease (AD), and Parkinson's disease (PD) are increasing gradually, reflecting a global threat vis‐à‐vis expressing the essentiality of a substantial paradigm shift in research and remedial actions. Protein glycation is influenced by several factors, like time, temperature, pH, metal ions, and the half‐life of the protein. Surprisingly, most proteins associated with metabolic and neurodegenerative disorders are generally long‐lived and hence susceptible to glycation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 397 publications
0
2
0
Order By: Relevance
“…Patients with PD often have comorbidities such as diabetes or hypertension due to age-related factors. Research ( 50 ) has found that PD shares common pathogenic mechanisms with diabetes in inflammation, oxidative stress, etc. Additionally, the use of antihypertensive drugs may sometimes exacerbate PD symptoms ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PD often have comorbidities such as diabetes or hypertension due to age-related factors. Research ( 50 ) has found that PD shares common pathogenic mechanisms with diabetes in inflammation, oxidative stress, etc. Additionally, the use of antihypertensive drugs may sometimes exacerbate PD symptoms ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…These transcription factors play crucial roles in the regulation of inflammatory gene expression. Thus the pathophysiology of chronic illnesses, such as diabetes [ 142 ], neurological disorders [ 62 ], cardiovascular diseases [ 135 ], and inflammatory conditions, is linked to the interaction between ROS and RAGE activation [ 143 ].…”
Section: Quantitative Assessment Techniques For Measuring Rage Activa...mentioning
confidence: 99%